Aries And Duby, Eds. A History Of Private Life. Volume I: From Pagan Rome To Byzantium, Veynem, Ed: Volume II: Revelations Of The Medieval World, Duby, Ed., - Dicks, Samuel (Teaching History: A Journal of Methods, 1994)
These are the first two volumes of a five volume series unique in their approach and scope in western historical scholarship. Later volumes, also now in print, come down to the present century. Originally published as Histoire de la vie privée and translated from the French by Arthur Goldhammer, they are lavishly illustrated with black-and-white and color pictures, diagrams, and other drawings.